IMPLEMENTASI KEBIJAKAN PROGRAM INDONESIA PINTAR PADA JENJANG SEKOLAH MENENGAH PERTAMA DI KABUPATEN BREBES (STUDI SMP NEGERI 3 SATU ATAP BANTARKAWUNG) - Lilian Haning Tyas; Dyah Lituhayu; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The Smart Indonesia Program (PIP) is a government program in the field of education as an effort to advance the quality of education in Indonesia. SMP Negeri 3 Satu Atap Bantarkawung is one of the schools in Brebes Regency whose students get PIP. This study aims to determine the implementation process and identify the supporting factors and inhibiting factors for PIP at SMP Negeri 3 Satu Atap Bantarkawung. This research uses descriptive qualitative method with purposive sampling technique. Sources of data through the results of interviews, observation and documentation. The results of this study indicate that PIP has been running well. The aim of PIP is to increase access to education, prevent children from dropping out of school due to economic difficulties and attract dropout students to return to education services. The characteristics of the implementing agency, communication, social, economic and political conditions are the driving factors. Discrepancies in the use of aid funds by the community, beneficiaries who were not fully on target, school delays in collecting files and delays in disbursement were the inhibiting factors. In this research, it was also found that cultural factors influenced the implementation of the Smart Indonesia Program policy, where people's perceptions of the reasons for dropping out of school were because people preferred to work outside the city to help their family's economy. Recommendations in the research are providing counseling to parents regarding the importance of education, efforts to monitor the use of PIP funds, updating and matching data to minimize inaccuracies in targeting recipients and encouraging a more role for BUMN in ensuring channeling banks to minimize delays in disbursement.